History and significance of National Development Service (NDS): Creating ’Civic Space’ and commitment to service in Nepal during the 1970s - Messerschmidt, Don; Yadama, Gautam; Silwal, Bhuvan (Occasional Papers in Sociology and Anthropology, 2008)
DOI: 10.3126/opsa.v10i0.1151 Occasional Papers in Sociology and Anthropology Vol.10 2007 p.174-207